A role of uroleuconaphins, polyketide red pigments in aphid, as a chemopreventor in the host defense system against infection with entomopathogenic fungi. (December 2018) - Horikawa, Mitsuyo; Shimazu, Mitsuaki; Aibe, Maki; Kaku, Hiroto; Inai, Makoto; Tsunoda, Tetsuto
Abstract Four red polyketide pigments, uroleuconaphins A1 (1 ) and B1 (2 ) and their glucosides3 and4, were isolated from the red goldenrod aphidUroleucon nigrotuberculatum . Although these red pigments exist only as glucosides3 and4 in the intact insect body, 3 and4 convert instantly to aglycones1 and2 at death. Pigments1 and2 inhibited the growth ofLecanicillium sp. (Ascomycota: Cordycipitaceae) and1, 2, and3 were active againstConidiobolus obscurus (Entomophthoromycota; Entomophthorales); these fungal species are pathogenic. We therefore regard aphid pigments1 –4 as chemopreventive agents that aid in the resistance of infection by entomopathogenic fungi at the level of the individual aphid and/or at the species level.